Gabriel Marcel Filsafat Eksistensi dan Konteks Kehidupan Bersama : Gabriel Marcel - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The context of living together always emphasize the one "We" and the whole. This is called the real intersubjectivity. Gabriel Marcel wish to stress that a base of genuine intersubjectivity is true love (agape). Fidelity, hope, presence, encounter, participation can attain its fundamental significance by true love. Problems that arise as obstacle to the esse as co-esse is fanatism, fundamentalism, terrorism, industrial technique progress of war equipment, war and arms bazaar. The existence philosophy of Gabriel Marcel intends to find a way to love, peace, friendship and unity. Thus, the philosophy of existence of Gabriel Marcel emphasizes humanity. The 'ethic-religion-raceclass' conflicts always become real problems in the community, but humanity is always one and whole. The objective of this research is an effort to discovery the meang and the basis of existence philosophy of Gabriel Marcel, so that it can facilitate the reflection on the concrete situation of nowadays as the context of co-esse. It shall present an originality description of the wiew of Gabriel Marcel and put forward its relevance to the context of social community today through new interpretation, insights and conclusions. This research use reflective and hermeneutic method. The result of this research even show that to be existentially human means being with the other in their diversity.